International Conference on Food Contaminants (ICFC 2017) : book of abstracts - Abrunhosa, L. (2018)
This conference follows the first ICFC, held in Lisbon, in 2015, which focused on the challenges in chemical mixtures. This second edition of ICFC is dedicated to present and discuss cutting-edge knowledge on climate changes and their impact on food safety issues. As accepted by the general scientific community, the global climate is changing, and Earth is becoming warmer. Climate change is also affecting the occurrence of food safety hazards at various stages of the food chain, from primary production to consumption. There are multiple pathways through which climate-related factors may impact food safety. The rising of CO2 levels is changing the temperature and precipitation patterns, increasing the frequency and intensity of extreme weather events. These changes are affecting the agricultural and animal production, the dissemination and incidence of crop diseases and pests, and the global food trade, in general.